2008
DOI: 10.1002/pola.22652
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembled organic nanotubes: Toward attoliter chemistry

Abstract: Diverse chemical functionalization of the inner and outer surfaces of the nanotubes enables us to sense and visualize the encapsulation and transport behavior of biomacromolecular guests. The event occurs specifically in attoliter volume nanospace inside the hollow cylinder of the nanotubes. Comparison of the organic nanotube history with that of well‐known carbon nanotubes and a variety of molecular building blocks as tube‐forming compounds were first introduced. Asymmetric organic nanotubes with different in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 91 publications
(110 reference statements)
1
54
0
2
Order By: Relevance
“…[5,6] As we know, nanotubes, which have hollow structure with less than 100 nm inner diameters, have highly potential applications in drug delivery and nanoobjects. [7] In addition, the helical nanostructures constructed from π-conjugated fluorescent LMWGs, such as twisted ribbons and fibers, are also a topic of increasing interest [8] due to their academic importance and promising applications in chiral recognition, optoelectronic devices and biomaterials. [9][10][11][12] Stimuli-responsive organogels are a kind of fascinating LMWGs in which the morphology of molecules is regulated by external stimuli, including light, [13,14] pH, [15,16] ions, [17,18] sound, [19,20] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] As we know, nanotubes, which have hollow structure with less than 100 nm inner diameters, have highly potential applications in drug delivery and nanoobjects. [7] In addition, the helical nanostructures constructed from π-conjugated fluorescent LMWGs, such as twisted ribbons and fibers, are also a topic of increasing interest [8] due to their academic importance and promising applications in chiral recognition, optoelectronic devices and biomaterials. [9][10][11][12] Stimuli-responsive organogels are a kind of fascinating LMWGs in which the morphology of molecules is regulated by external stimuli, including light, [13,14] pH, [15,16] ions, [17,18] sound, [19,20] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…MONT is a good template potential for the preparation of PNT because of simple preparation process and cheap raw materials. Shimizu group reported several MONT systems prepared by adding metal ions into the self-assembling system of amphiphilic molecules with different carbon chains [15][16][17][18]. The MONTs with various metal ions on the surface were successfully obtained.…”
Section: Introductionmentioning
confidence: 99%
“…32 The details of the nano-bio applications of a variety of self-assembled nanotubes are reviewed elsewhere. 33 …”
Section: Unique Properties and Encapsulation Functions Of Hollow Cylimentioning
confidence: 99%
“…In particular, capillary action allows us to effectively fill the nanotubes with, for example, gold nanoparticles (1-50 nm), 92,93 cadmium sulfide (2-3 nm), 87 magnetite (ca. 10 nm), 33 spherical protein Ferritin (12 nm), 94 and green fluorescent protein (GFP, 3 Â 4:5 nm) ( Figure 15). We have also reported that electrostatic interaction between the guests and inner surfaces of the nanotubes is also critical to promote the encapsulation of such guests without depending on capillary force.…”
Section: Unique Properties and Encapsulation Functions Of Hollow Cylimentioning
confidence: 99%
See 1 more Smart Citation